Training and Motivation in Improving Students' Entrepreneurial Competence in the Digital Era - Ellen Rusliati; Liza Laila Nurwulan; R. Moch. Noch; Ruslina Lisda; M. Ichsan Rauf (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2026)
The advancement of digital technology has brought changes in the world of entrepreneurship. For high school students, entrepreneurial competence is an important skill to be developed from an early age. The purpose of this community service is to provide training and motivation in improving students' entrepreneurial competence in the digital era, emphasizing the importance of adapting to technology, creativity, and a proactive attitude. The methods used were lectures, mentoring, monitoring, and evaluation involving five lecturers and 171 students of SMAN 5 Cimahi City. The results show that there is an increase in student entrepreneurial competence in the digital era. Things that still need to be improved include opportunity analysis, flexible business plans in accordance with changing market conditions, and determining customer segments. Training and motivation are two important pillars in shaping students' entrepreneurial competencies, especially in the digital era that demands high flexibility and innovation. Schools need to integrate training programs that are relevant to technological developments, as well as encourage a learning environment that motivates students to become adaptive and creative young entrepreneurs.